Moisture Sources for the Explosive Cyclogenesis of Extratropical Cyclone Miguel (2019) through a Lagrangian Approach - Patricia Coll-Hidalgo; Albenis Pérez-Alarcón; José Carlos Fernández-Alvarez; Raquel Nieto; Luis Gimeno (Environmental Sciences Proceedings, 2021)
In this study, the moisture sources for the explosive cyclogenesis Miguel that occurred during 4–9 June 2019 in the North Atlantic were investigated. To determine the moisture sources, the Lagrangian FLEXPART particle dispersion model was used. The moisture uptake pattern revealed the western North Atlantic Ocean extending to north-western North America, the south-eastern coast of Greenland, and the central North Atlantic Ocean around 45° N and 50°–20° W as the main moisture sources for Miguel explosive cyclogenesis. Furthermore, the moisture uptake from these regions was higher than the climatology. During the intensification of Miguel, the moisture contribution from oceanic sources was higher than terrestrial sources. Although the total amount of atmospheric moisture achieved during the explosive intensification was similar to that absorbed the 24 h prior, they changed in intensity geographically, being more intense the local support over central and northern North Atlantic basin.